A framework for marketing management - Kotler, Philip (Prentice Hall, 2001)
A Framework for Marketing Management is a concise paperback adapted from Philip Kotler's #1 selling book, Marketing Management. A four-part organization covers understanding marketing management, analyzing marketing opportunities, making marketing decisions, and managing and delivering marketing programs. Readers will be able to see how marketing managers have applied key principles in actual company situations, making explicit the connection between theory and implementation at leading firms such as eBay, NTT DoCoMo, Caterpillar, and Starbucks. For anyone interested in the field of marketing—and its relationship with the consumer.